CUPPING AND FEMALE REPRODUCTIVE PROBLEMS: A NARRATIVE REVIEW - Dewi Anggraini Padmaningtyas; Sesaria Lukman; Andari Wuri Astuti; Septiana Ade Amalia (International Islamic Medicine Forum, 2024)
Al-hijamah, or cupping therapy, uses a cupping device to vacuum suction the skin. The recommendation and virtues of cupping are found in various hadiths of the Messenger of Allah (peace and blessings of Allah be upon him). It has been used traditionally for centuries and is gaining recognition for its potential health benefits, especially in women's reproductive health. The aim of this review is to map the research results on the cupping method (Al-hijamah) as an evidence-based treatment method for addressing reproductive problems in women. This narrative review uses databases, including PubMed, ScienceDirect, EBSCO, and Grey Literature, as well as Google Scholar and Research Rabbit. Based on the results of the inclusion and exclusion criteria, 13 articles were retrieved, and 2 themes were obtained, namely the role of cupping therapy for women's reproductive health and various combinations of cupping with other methods. Cupping therapy can have a positive impact on various aspects of female reproductive health, including menstrual disorders and infertility. Studies have shown improvements in menstrual cycles, reduction in menstrual pain, and increased fertility rates in women who undergo cupping therapy. In addition, cupping therapy has also shown promise in treating conditions such as Polycystic Ovarian Syndrome (PCOS) and anemia associated with excessive menstrual bleeding.